A Review on the Phytochemical and Pharmacological Activitities of Luffa acutangula (L.) Roxb. - Erna Harfiani; Dhigna Citra Pradana; Hany Yusmaini (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2020)
Indonesia is a country with a tropical climate, so it can be a place to live for various plants in the world. The use of plants in Indonesia as an alternative treatment requires a lot of research because many plants have not been studied for their chemical compounds and pharmacological effects. Ethnopharmacological studies of a plant can be the basis for medicinal plant research. Empirically, Luffa acutangula (L.) Roxb. (angled luffa, gambas) is a plant that has various therapeutic benefits. This study aimed to determine pharmacognostic properties (macroscopic and microscopic fradments of crude drugs), chemical compound content, and pharmacological activity of L. acutangula extract in literature studies. Literature searching were performed by online searching using Google Scholar, Science Direct, and PubMed as the databases. L. acutangula has been used empirically in Indonesia for helping in the treatment of various diseases. The phytochemical content of L. acutangula extract will affect its pharmacological activity. Phytochemical analysis of L. acutangula leaf powder, namely there are chemical compounds of alkaloids, glycosides, saponins, carbohydrates, amino acids, and lipids. Analysis of the ethanol extract of L. acutangula contained chemical compounds of alkaloids, glycosides, saponins, carbohydrates, and steroids. Analysis of the aqueous extract of L. acutangula contained alkaloids, saponins, carbohydrates, terpenoids, and triterpenoids. The pharmacological activities of L. acutangula included antimicrobial, anticancer, antioxidant, hypoglycemic, hepatoprotective, gastroprotective, immunomodulatory, antiparasitic, anti-inflammatory, analgesic, and anti-thyroid. L. acutangula which contain various phytochemical compounds is potentially to be further studied to develop its pharmacological benefits.